"New Leadership", Leader-Member exchange And Commitment To Change: The Case Of Higher Education In Malaysia. - May, Chiun Lo; Ramayah, T.; Cyril de Run, Ernest; Voon, Mung Ling (2009)
Human resource management faces challenges of bringing better fitted workers into the organizations and of meeting the workers' needs and expectations.